Early outcomes of conformal radiotherapy in the treatment of cavernous sinus meningioma. Issue 2 (23rd October 2018) - Moujahed, R.; Ghedira, K.; Drissi, C.; Kallel, A.; Kochbati, L.
Abstract: Aim : Cavernous sinus tumours represent 1% of all intracranial neoplasms, and 41% of them are cavernous sinus meningiomas (CSM). The disappointing results of the microsurgical approach in the treatment of CSM have led to the evaluation of a more conservative strategy, such as conformal radiotherapy (CR) and stereotactic radiosurgery (SRS). Here we report our experience with CR in the treatment of CSM, aiming to evaluate local control, clinical response and radiation-induced toxicity. Methods : A total of 18 patients with CSM, treated from 2011 to 2017, were retrospectively reviewed. Results : Patient median age was 59 years [31–74]. Clinical presentation included impaired vision, cranial nerve deficit, headache, ocular signs. Median tumour size was 35 mm [13–56]. Six patients were operated before the radiation. Twelve patients were treated with definitive radiotherapy. Dose of radiation varied from 50.4 Gy in 28 fractions, to 54 Gy in 30 fractions. Median follow-up was 33 months [6–84]. Among the 18 patients, patient's signs and symptoms of disease remained unchanged in three cases (16.66%), 12 (66.66%) were improved and 1 patient (5.55%) exhibited tumour progression (exophthalmia). Two patients (11.11%) were lost to follow-up after the end of the treatment with radiotherapy. Findings : Based on our study findings, CR has proved to be a relatively safe and effective therapeutic option in the treatment of CSM, whether used as first-line or as an adjuvant treatment. CR may be particularly effective for tumours that are not amenable to SRS, owing to lesion size (> 30-35 mm) and/or proximity to the optic apparatus (<3 mm).